Above the invasive and ornamental attributes of the travelers palm: an In vitro and In silico insight into the anti-oxidant, anti-enzymatic, cytotoxic and phytochemical characterization of Ravenala madagascariensis - Suroowan, Shanoo; Llorent-Martínez, Eulogio Jose; Zengin, Gokhan; Dall’Acqua, Stefano; Sut, Stefania; Buskaran, Kalaivani; Fakurazi, Sharida; Le Van, Bao; Abdalla, Mohnad; Abdalla, Ashraf N.; Khalid, Asaad; Mahomoodally, Mohamad Fawzi (Multidisciplinary Digital Publishing Institute, 2023)
Ravenala madagascariensis is a widely known ornamental and medicinal plant, but with a dearth of scientific investigations regarding its phytochemical and pharmacological properties. Hence, these properties were appraised in this study. The DPPH (154.08 ± 2.43 mgTE/g), FRAP (249.40 ± 3.01 mgTE/g), CUPRAC (384.57 ± 1.99 mgTE/g), metal chelating (29.68 ± 0.74 mgEDTAE/g) and phosphomolybdenum assay (2.38 ± 0.07 mmolTE/g) results demonstrated that the aqueous extract had the most prominent antioxidant activity, while the methanolic extract displayed the best antioxidant potential in the ABTS assay (438.46 ± 1.69 mgTE/g). The HPLC-ESI-Q-TOF-MS-MS analysis allowed the characterization of 41 metabolites. The methanolic extract was the most active against acetylcholinesterase. All extracts were active against the alpha-amylase and alpha-glucosidase enzymes, with the ethyl acetate extract being the most active against the alpha-amylase enzyme, while the methanolic extract showed the best alpha-glucosidase inhibition. A plethora of metabolites bonded more energetically with the assayed enzymes active sites based on the results of the in silico studies. R. madagascariensis extracts used in this study exhibited cytotoxicity against HT29 cells. The IC50 of the methanolic extract was lower (506.99 ug/mL). Based on the heat map, whereby flavonoids were found to be in greater proportion in the extracts, it can be concluded that the flavonoid portion of the extracts contributed to the most activity.